Turning to friends in preference to parents for support in early adolescence: does this contribute to the gender difference in depressive symptoms? - Nicky Wright; Helen Sharp; Jessica Gay; Andrew Pickles; Jonathan Hill (Frontiers in Child and Adolescent Psychiatry)
IntroductionBased on established evidence of gender differences in friendship patterns, and the vulnerability associated with early reliance on friends, we hypothesized that in 13-year-olds, a preference for turning to friends rather than parents for emotional support contributes to the gender difference in depressive symptoms.MethodsUsing a cross-sectional design, 671 adolescents (53.7% girls; mean age 13.11 ± 0.52 years) in a UK birth cohort [Wirral Child Health and Development Study (WCHADS)] reported turning to their parents and to their friends when distressed [Network of Relationships Inventory (NRI)] and depressed [Short Mood and Feelings Questionnaire (SMFQ)]. Preferentially turning to friends was assessed as turning to friends minus turning to parents for support. Analyses used path analysis using the gsem command in Stata.ResultsGirls had higher depressive symptoms than boys (p < .001). Consistent with the hypotheses, girls had higher scores than boys for preferentially turning to friends (p < .001). Preferentially turning to friends was associated with higher depressive symptoms (p < .001), and this mediated the gender difference in depressive symptoms (p < .001). The association between preferentially turning to friends and depressive symptoms was stronger for girls than for boys (p = .004).ConclusionsIn young adolescents, preferentially turning to friends over parents when distressed is common, and the association between preferentially turning and depressive symptoms is markedly higher in girls than in boys. This reflects either a gender difference in social vulnerability to depression or a greater impact of depression on the reliance on friends instead of parents in girls. While clarifying the directions of influence requires prospective study, these findings provide the first evidence that the assessment of depression in young adolescents should consider the degree of reliance on friends and parents.